Digital Nudging in Social Media Disaster Communication - Milad Mirbabaie; Christian Ehnis; Stefan Stieglitz; Deborah Bunker; Tanja Rose (Information Systems Frontiers, 2020)
Social media has become an important channel of communication in emergency and disaster management. Emergency Management Agencies can distribute helpful and important information to the general public and also gather information to enrich their management efforts. This, however, remains challenging since several communication-related barriers occur. This study investigates how the concept of Nudging, a form of behaviour adjustment, can be applied to address these barriers. A Systematic Literature Review and qualitative social media data analysis methods were applied to explore the potential of digital nudges on social media. Twelve forms of digital nudges could be identified in the data that influenced the visibility of the messages they occurred in. The results suggest that Digital Nudging on Social Media is a promising approach to use in emergency and disaster communication.
Keywords: 000; Digital nudging; Social media; Disaster communication; Emergency management